1988
DOI: 10.1111/j.1365-2133.1988.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with n-3 fatty acids on clinical manifestations of psoriasis

Abstract: In a double-blind, block randomized study we investigated the effect of dietary supplementation with eicosapentaenoic acid in patients with psoriasis. The experimental group received 10 g of fish oil daily containing approximately 1.8 g eicosapentaenoic acid, while the controls were given an isoenergetic amount of olive oil. We found no significant change in the clinical manifestations of psoriasis in either group after 8 weeks of treatment. In the experimental group, the amount of n-3 fatty acids in serum pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 12 publications
1
52
1
4
Order By: Relevance
“…Adil et al observed a 50% reduction in the PASI score in nearly half of patients after 12 weeks of omega-3 supplementation at a dose of 1.8 g/day [92]. However, not all data are consistent, for example in terms of reduction of individual PASI components or the efficacy of supplementation as such [82,93].…”
Section: Dieta W łUszczycymentioning
confidence: 99%
“…Adil et al observed a 50% reduction in the PASI score in nearly half of patients after 12 weeks of omega-3 supplementation at a dose of 1.8 g/day [92]. However, not all data are consistent, for example in terms of reduction of individual PASI components or the efficacy of supplementation as such [82,93].…”
Section: Dieta W łUszczycymentioning
confidence: 99%
“…Veale et al 6 reported no significant changes in articular index or skin itch at the end of the study, yet the subjects in the active treatment group had significantly more skin itch at the beginning (P = 0.03), thus suggesting the implementation of n-3 PUFA may be helpful for skin itch. Although Bjorneboe et al 14 did not find any significant difference between both groups, the total n-3 PUFA in serum phospholipids was significantly increased as compared to pre-treatment values while causing a significant fall in the AA and linoleic acid content of serum phospholipids. Madland et al 15 reported a significant improvement of joint pain in patients with psoriatic arthritis in both intervention and control groups; only improvement of joint swelling was noted in the intervention group.…”
Section: Description Of Included Studiesmentioning
confidence: 81%
“…LTB4 was found to have significantly decreased in the treatment group (P < 0.03) but not in the control group. The other six studies 5,6,14,15,17,18 reported no significant reduction in scaling, erythema, area involved or thickness. Gupta et al 5 reported the mean time period elapsed before the psoriasis worsened to pre-therapy severity was 4.9 AE 0.5 weeks in the intervention group and 4.5 AE 0.6 weeks in the control group (P = 0.4).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan bir çalışmada sekiz hafta boyunca on üç hastaya 1,8 g/gün EPA içeren balık yağı ve on dört hastaya zeytinyağı verilmiştir. EPA verilen grupta serum fosfolipitlerinde artış görülürken, klinik parametrelerinden eritem, infiltrasyon, deskumasyon, hastalığın vücudu kaplama alanı, PAŞİ ve sübjektif skorlarında anlamlı bir değişiklik saptanmamıştır (14). Yapılan bir çiftkör çalışmada n-3 yağ asitlerinden zengin balık yağı ve n-6 yağ asitlerinden zengin yağ ile yapılan kombine tedavi sonrasında kronik stabil plaklı psoriasisli hastaların klinik bulgularında hiçbir değişiklik görülmemiştir (15).…”
Section: Psoriasis Ve Beslenme İlişkisi çOklu Doymamış Yağ Asitleri Vunclassified